Effectiveness of low‐dose intravenous immunoglobulin therapy in minor primary antibody deficiencies: A 2‐year real‐life experience. (28th June 2021) - Vivarelli, Emanuele; Matucci, Andrea; Bormioli, Susanna; Parronchi, Paola; Liotta, Francesco; Cosmi, Lorenzo; Almerigogna, Fabio; Vultaggio, Alessandra
Abstract: Primary antibody deficiencies (PAD) are the most prevalent group of primary immunodeficiencies (PID) in adults and immunoglobulin replacement therapy (IRT) is the mainstay therapy to improve clinical outcomes. IRT is, however, expensive and, in minor PAD, clear recommendations concerning IRT are lacking. We conducted a retrospective real‐life study to assess the effectiveness of low‐dose IRT in minor PAD on 143 patients fulfilling European Society for Immunodeficiencies (ESID) diagnostic criteria for immunoglobulin (Ig)G subclass deficiency (IgGSD) or unclassified antibody deficiency (UAD). All patients were treated with intravenous low‐dose IRT (0.14 ± 0.06 g/kg/month). Immunoglobulin (Ig) classes and IgG subclasses were measured at baseline and after 1 year of IRT. The annual rate of total infections, upper respiratory tract infections (URTI), lower respiratory tract infections (LRTI) and hospitalizations was measured at baseline and after 1 and 2 years of IRT. After 1 year of IRT significant improvement was demonstrated in: (a) serum IgG (787.9 ± 229.3 versus 929.1 ± 206.7 mg/dl; p  < 0.0001); (b) serum IgG subclasses (IgG1 = 351.4 ± 109.9 versus 464.3 ± 124.1, p  < 0.0001; IgG2 = 259.1 ± 140 versus 330.6 ± 124.9, p  < 0.0001; IgG3 = 50.2 ± 26.7 versus 55.6 ± 28.9 mg/dl, p  < 0.002); (c) annual rate of total infections (5.75 ± 3.87 versus 2.13 ± 1.74, p  < 0.0001), URTI (1.48 ± 3.15 versus 0.69 ± 1.27; p  < 0.005), LRTI (3.89 ± 3.52 versus 1.29 ± 1.37; p  < 0.0001) and hospitalizations (0.37 ± 0.77 versus 0.15 ± 0.5; p  < 0.0002). The improvement persisted after 2 years of IRT. No significant improvement in URTI annual rate was noted in UAD and in patients with bronchiectasis. In conclusion, low‐dose IRT can improve clinical outcomes in UAD and IgGSD patients, providing a potential economical advantage over the standard IRT dose. Abstract : In our retrospective real‐life study we assessed the effectiveness of low‐dose intravenous immunoglobulin replacement therapy (IRT) on 143 patients fulfilling ESID diagnostic criteria for IgG subclass deficiency (IgGSD) or Unclassified Antibody Deficiency (UAD). After one year of low‐dose IRT significant improvement was demonstrated in: a) serum IgG; b) Serum IgG subclasses; c) annual rate of total infections, upper and lower respiratory tract infections and hospitalizations. The improvement persisted after two years of IRT. In conclusion, low‐dose IRT can improve clinical outcomes in UAD and IgGSD patients, with significant cost reduction in comparison to the standard IRT dose.